Cross-Cultural Reading Comprehension Assessment in Malay and English as it Relates to the Dagostino-Carifio Model of Reading Comprehension - Lorraine Dagostino; James Carifio; Jennifer D. C. Bauer; Qing Zhao (Arizona State University, 2013)
The review of existing literature suggests that few researchers have adopted cross-language comparisons to explore how cultural background affects the assessment of reading comprehension of students.  In this present study, the researchers independently reviewed and rated all the items of two reading comprehension tests translated from Malay into English. The original tests, based upon Dagostino-Carifio's (1994) model of reading comprehension, were developed in Malaysia for the purpose of evaluating reading comprehension abilities of K-6 students in Malaysia.  Results indicated that some information in the test material are culturally based and are lost in translation. Findings imply the possibility of employing comparable tests with valid translation to evaluate reading comprehension abilities of second language (L2) students.